FAKTOR YANG MEMPENGARUHI PENYALURAN KREDIT INVESTASI PADA BANK UMUM DI INDONESIA - Ika Chusniah; Syamsul Hadi (Jurnal Ilmu Ekonomi JIE, 2018)
study aims to analyzing the progress of credit invesment distribution also third-party fund, Capital Adequacy Ratio (CAR) and Loan to Deposit Ratio (LDR) effects toward credit invesment on commercial bank in Indonesia. This study data collection using secondary data directly from Bank Indonesia  official websites and Indonesian Banking Statistic. Tools used in this analysis is multiple linear regression with time series data. The results of this study shows that third-party fund have positive and significant effects toward credit invesment distribution with coefficient value amount 1.1761 and probability value 0.0000. Capital Adequacy Ratio (CAR) have negative and insignifficant coefficient regression value amount -0.0005 and probability value amount 0.3749. Loan to Deposit Ratio toward credit invesment distribution with coefficient regression value amount 0.0243 and probability value 0.0000. Keywords: third-party fund, Capital Adequacy Ratio, Loan to Deposit Ratio